Impact of life skill development program to improve teaching skills of teacher trainees - Babu, Binu; Charles, M. Aron Antony (Edelweiss Applied Science and Technology, 2024)
For teacher trainees to have effective lives, life skill education is essential to fostering their psychological health and sense of fulfilment in life. This study investigates the impact of a Life Skill Development Program (LSDP) on enhancing the teaching skills of teacher trainees in Kerala, focusing on key competencies such as classroom management, lesson planning, communication skills, student engagement, problem-solving, and emotional intelligence. The study also examines how specific components of the LSDP—such as problem-solving, communication skills training, and decision-making training, and emotional intelligence training—affect teaching performance. Additionally, the influence of demographic variables (age, gender, prior teaching experience, and educational background), the mode of program delivery (in-person vs. online), and the level of trainee participation are analyzed. The research design, incorporating both quantitative and qualitative approaches. Data were collected through structured questionnaires and interviews with 100 teacher trainees who participated in the LSDP. Statistical tools such as Paired Sample t-test, Multiple Regression Analysis, ANCOVA, and Pearson Correlation were employed to test the hypotheses and analyze the data. The results indicate that the LSDP has a positive impact on the overall teaching skills of teacher trainees, with higher levels of engagement leading to greater improvements. The study also reveals that in-person training is more effective than online delivery in developing teaching skills. These findings highlight the critical role of life skill training in improving the professional competencies of future educators, with implications for the design and delivery of teacher training programs.